Estudo cinético da hidrogenação catalítica do CO2 sobre Ru/SiO2 - Cabral, Thiago Oliveira (2019)
One of the new processes and technologies that aim the utilization or transformation of CO2 into more valuable products processes is the CO2 catalytic hydrogenation into CH4. The purpose of this work was to investigate the kinetics of CO2 catalytic hydrogenation, varying CO2 partial pressure (4,1 – 32,4 kPa), H2 partial pressure (25,3 – 75,9 kPa) and calculating the turnover frequencies (TOF) of the reaction products (CH4, CO and H2O). The reaction was conducted under steady state, kinetic regime, differential reactor and different temperatures (275, 300, 325 e 350°C). A Ru/SiO2 catalyst was synthetized by wet impregnation and characterized by the XRF, XRD, TPRH2, N2 physisorption, TEM, H2 and CO chemisorption and TGA techniques. Spectroscopic evidences about the surface reaction were obtained by DRIFTS, revealing the presence of active and inactive CO species adsorbed onto Ru nanopoarticles and at the inerface, as well as adsorbed formate and bicarbonate on the support. Kinetic measurements showed that the CH4 turnover frequency and selectivity towards methanation is maximized for higher H2 pressures, lower CO2 pressures and lower temperatures. Through mechanistic modelling and parameter estimation, it was verified that a model which contemplates the dissociative adsorption of CO2 over Ru sites (and assumes that either the direct hydrogenation of the reative CO* species or the H-assisted reductive dissociation of the HCO* species would be the rate-determining steps) fitted to experimental TOFCH4 data in a more statistically representative manner than other models derived from a bicarbonate-formate-CO* reative-CH4 mechanistic route, allowing a reasonable physical and phenomenological interpretation of the parametric estimates.